Evaluation of leachate characteristics from different leachate ponds in a semi-aerobic landfill - Olisa, E. (Trans Tech Publications Ltd, 2016)
In this study, the performance of a semi-aerobic landfill was monitored through the analysis of leachate composition collected from different leachate ponds; collection pump (CP), equalization pond (EQ) and aerated pond (AP). The landfill site is located in the tropical environment of the central region of Malaysia. Malaysia has adopted the semi-aerobic system of landfill; however this landfill produces leachate with high organic matter content which can be converted to methane gas under anaerobic condition and it also allows the escape of landfill gas (LFG) from the leachate collection pipes. Twenty parameters were analyzed and the mean values of the parameters for leachate at the CP, EQ and AP, which include; pH (8.24, 8.00 and 8.73), total kjeldahl nitrogen (3987.25, 8744.6, 1927.31 TKN-N), ammonia-N (3726, 3800, 1560 mg/L NH3- N), nitrate (26.7, 33.3, 25 mg/L NO3-N), total phosphorus (0.85, 0.78, 0.92 mg/L PO43-), BOD5 (305, 311.3, 201 mg/L), COD (16100, 14587, 12780 mg/L), BOD5/COD (0.019, 0.021, 0.016), turbidity (405, 735, 940 NTU), colour (3991, 4122, 3412 Pt Co), TSS (109.3, 58, 50.7 mg/L), EC (32.8, 21.9, 37.0 mS/cm) and TDS (21.98, 14.7, 24.8 mg/L) were recorded appropriately. The results realized from the analysis of the three ponds were compared with data published by other researchers and also the standards specified by the Malaysia Environmental Quality (MEQ) Act 1974. The results obtained indicate that the leachate from the aerated pond could remove some of the pollutants and was better stabilized as compared to the leachate from the pump and equalization ponds. It is also found that the aeration process in aerated pond could enhance the reduction of pollutants in the leachate. The measured leachates would require appropriate treatment methods in order to reduce the pollutants to meet the discharge standard before releasing them into water courses. Â© 2016 Trans Tech Publications, Switzerland.